Restricting Symptoms in the Last Year of Life: A Prospective Cohort Study - Chaudhry, Sarwat I. (2013)
IMPORTANCE: Freedom from symptoms is an important determinant of a good death, but little is known about symptom occurrence during the last year of life. OBJECTIVE: To evaluate the monthly occurrence of physical and psychological symptoms leading to restrictions in daily activities (ie, restricting symptoms) among older persons during the last year of life and to determine the associations of demographic and clinical factors with symptom occurrence. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study. Comprehensive assessments were completed every 18 months, and monthly interviews were conducted to assess the presence of restricting symptoms. Of 1002 nondisabled community-dwelling individuals 70 years or older in greater New Haven, Connecticut, eligible to participate, 754 agreed and were enrolled between 1998 and 1999. MAIN OUTCOMES AND MEASURES: The primary outcome was the monthly occurrence of restricting symptoms as a dichotomous outcome. The monthly mean count of restricting symptoms was a secondary outcome. RESULTS: Among the 491 participants who died after their first interview and before June 30, 2011, mean age at death was 85.8 years, 61.9% were women, and 9.0% were nonwhite. The mean number of comorbid conditions was 2.4, and 73.1% had multimorbidity. The monthly occurrence of restricting symptoms was fairly constant from 12 months before death (20.4%) until 5 months before death (27.4%), when it began to increase rapidly, reaching 57.2% in the month before death. In multivariable analysis, age younger than 85 years (odds ratio [OR], 1.30 [95% CI, 1.07–1.57]), multimorbidity (OR, 1.38 [95% CI, 1.09–1.75]), and proximity to time of death (OR, 1.14 per month [95% CI, 1.11–1.16]) were significantly associated with the monthly occurrence of restricting symptoms. Participants who died of cancer had higher monthly symptom occurrence (OR, 1.80 [95% CI, 1.03–3.14]) than participants who died of sudden death, although this difference was only marginally significant (P = .04). Symptom burden did not otherwise differ substantially according to condition leading to death. CONCLUSIONS AND RELEVANCE: Restricting symptoms are common during the last year of life, increasing substantially approximately 5 months before death. Our results highlight the importance of assessing and managing symptoms in older patients, particularly those with multimorbidity.